Numerical modelling of matric suction in unsaturated soil under shallow foundation under varying soil and hydrological conditions - Muhammad Rehan Hakro; Zaheer Almani; Muhammad Ahsan Channa; Junaid Jokhioc (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent times, extreme hydrological events have disrupted the performance of various structures, particularly the structural foundations responsible for transferring the superstructure’s weight to the natural ground. This disruption underscores the significance of matric suction and soil saturation, which are influenced by hydrological conditions like precipitation, soil shear strength, and foundation settlement. These factors are essential when designing structures in specific locations with distinct geotechnical parameters. To address these challenges, our research employs Plaxis 2D numerical modeling to investigate the dynamic changes in matric suction within soil beneath shallow foundations under varying rainfall conditions. Our approach involves a fully-coupled flow method, incorporating the Van Genuchten hydraulic model. In recognition of practical constraints, we utilize fundamental soil classification parameters for model configuration. Our findings reveal the substantial impact of matric suction fluctuations during rainfall on soil deformation, as indicated by displacement patterns. This highlights the critical importance of matric suction in comprehending soil behavior. Furthermore, we observe that higher initial water table levels correlate with reduced variations in matric suction and soil deformation during rainfall, emphasizing the regulatory role of water table depth. In conclusion, this study emphasizes the necessity of considering matric suction and water table depth in structural design and geotechnical analysis, particularly when faced with extreme hydrological events. By comprehending these factors, we can enhance our understanding of soil behavior, improve foundation stability, and develop more effective design strategies for structures in various environmental conditions.